1985
DOI: 10.1093/oxfordjournals.jbchem.a135290
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of myo-Inositol-1-Phosphatase from Rat Brain

Abstract: myo-Inositol-1-phosphatase [EC 3.1.3.25] was purified from a cytosolic fraction of rat brain. The purified enzyme appeared homogeneous on SDS-polyacrylamide gel electrophoresis and its molecular weight was estimated to be 29,000. The molecular weight of the native enzyme was 55,000 as determined by molecular sieve chromatography. These values indicated that the native enzyme was composed of two identical subunits. The isoelectric point of the enzyme was 4.6. The enzyme hydrolyzed inositol-1-phosphate, 2'-AMP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
59
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 0 publications
14
59
1
Order By: Relevance
“…Mammalian inositol monophosphatases have been shown to have a relatively broad substrate specificity and can hydrolyze a variety of phosphate compounds other than inositol monophosphatase (6,7,11,16,24,37). For instance, the enzyme from rat testis hydrolyzes adenosine 2Ј-monophosphate with a relative velocity of 38% (6) and the enzyme from bovine brain hydrolyzes ␤-glycerophosphate and adenosine 2Ј-monophosphate with relative velocities of 33 and 50%, respectively (7).…”
Section: Resultsmentioning
confidence: 99%
“…Mammalian inositol monophosphatases have been shown to have a relatively broad substrate specificity and can hydrolyze a variety of phosphate compounds other than inositol monophosphatase (6,7,11,16,24,37). For instance, the enzyme from rat testis hydrolyzes adenosine 2Ј-monophosphate with a relative velocity of 38% (6) and the enzyme from bovine brain hydrolyzes ␤-glycerophosphate and adenosine 2Ј-monophosphate with relative velocities of 33 and 50%, respectively (7).…”
Section: Resultsmentioning
confidence: 99%
“…In the experiments where the effect of Li+ was investigated, 5 X lo-' moL4 LiCl or 5X moVl NaCl in control incubations was included from the sedimentation step onwards on the second day. Li+ uncompetitively inhibits inositol-I-phosphatase from rat brain and inositol polyphosphate Iphosphatase from calf brain with 50% inhibition at 1-6X mol/ 1 (Takimoto et al 1985;Inhorn & Majerus 1987), indicating that 5X mol/l Li+ should inhibit substantially the degradation of inositol phosphates.…”
Section: Methodsmentioning
confidence: 99%
“…The other major reason for the interest in this enzyme is that it is inhibited by Li' (Naccarato et al, 1974;Hallcher & Sherman, 1980;Takimoto et al, 1985). This -inhibition is interesting since it has been found that Li+, which is widely used in the treatment of manic depression, causes a rise in the cortical concentration of InsI-P in rat brain on both acute (Allison et al, 1976) and chronic (Sherman et al, 1981) treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This -inhibition is interesting since it has been found that Li+, which is widely used in the treatment of manic depression, causes a rise in the cortical concentration of InsI-P in rat brain on both acute (Allison et al, 1976) and chronic (Sherman et al, 1981) treatment. Takimoto et al (1985) have purified the rat brain myoinositol-l-phosphatase and have reported some of its properties. Most of the work on the bovine enzyme reported to date has been performed on fairly crude enzyme preparations from bovine brain, with specific activities of about 45 units (1 unit corresponds to release of 1 /tmol of P,/h at 37°C)/mg (Hallcher & Sherman, 1980;Ackerman et al, 1987).…”
Section: Introductionmentioning
confidence: 99%